PENELITIAN KEWIRAUSAHAAN DI INDONESIA : PEMETAAN PUBLIKASI DALAM PERSPEKTIF SCIENTOMETRIK (1972-2019) - Agung Purnomo; Indrianawati Usman; Nur Asitah (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2019)
Entrepreneurship in Indonesia continues to grow and develop. However, there were no studies that review and map entrepreneurial studies from Indonesian affiliated researchers with data from year to year. This research aims to map entrepreneurial research by Indonesian institutional affiliated researchers that was published internationally in the Scopus indexed in a Scientometric perspective. The study conducted a bibliometric method and analyzed research data using the analyze search results service from Scopus and the VOSviewer application. Research data of 947 academic documents published from 1972 to 2019 were obtained from the Scopus database in December 2019. The results showed the most productive Indonesian-affiliated institutions and individual researchers in entrepreneurship publications were Institut Teknologi Bandung and Grisna Anggadwita. The subject area and sources of the most publications of entrepreneurship were business, management, and accounting; and proceedings of the IOP Conference Series: Materials Science and Engineering. There were five groups of research keywords, and three collaboration patterns of Indonesian affiliated researchers in the field of entrepreneurship. Kewirausahaan di Indonesia kian tumbuh dan berkembang. Namun, belum ada penelitian yang mengulas dan memetakan studi kewirausahaan hasil peneliti berafiliasi Indonesia dengan data dari tahun ke tahun. Riset ini bertujuan untuk memetakan penelitian kewirausahaan oleh peneliti berafiliasi institusi Indonesia yang dipublikasikan internasional bereputasi terindeks Scopus dalam perspektif Scientometrik. Studi melakukan metode bibliometrik dan menganalisis data penelitian menggunakan layanan analyze search results dari Scopus dan aplikasi VOSviewer. Data penelitian 947 dokumen akademik yang diterbitkan dari tahun 1972 hingga tahun 2019 yang diperoleh dari database Scopus pada bulan Desember 2019. Hasil penelitian menunjukkan institusi dan individu peneliti berafiliasi Indonesia paling produktif dalam publikasi bidang kewirausahaan adalah Institut Teknologi Bandung dan Grisna Anggadwita. Bidang studi dan sumber publikasi terbanyak ranah kewirausahaan adalah bisnis, manajemen, dan akuntansi; dan prosiding IOP Conference Series: Materials Science and Engineering. Ada lima kelompok kata kunci penelitian, dan tiga pola kolaborasi peneliti berafiliasi Indonesia pada bidang kewirausahaan.